Reclosing transients in standard and premium efficiency induction machines in the presence of voltage unbalance - Gabaraane, Tumelo (Department of Electrical Engineering, 2019)
The impact of restarting an induction machine, while coasting, was investigated in this study. When restarting an induction machine, high peaking current and torque transients appear. As a result, possible damage to the rotor shaft could occur together with a destabilising of the power system which could lead to fluctuating supply voltage levels. This dissertation investigated the restarting of two different efficiency class induction machines and analyses how a shift in the phase between the supply voltage and the residual voltage affects the restarting transients. Previous studies have been carried out on standard efficiency induction machines, however this study aimed to compare the impact of restarting on the standard and premium plus efficiency induction machines. The design differences between standard and energy efficient induction machines play a significant role in how these transients behave. The energy efficient machines were found to be made of higher grade lamination steel and larger sized conductors in order to reduce the stator and rotor copper losses. Using material with a higher permeability, as is the case with energy efficient machines, ensures that the machines are able to retain less residual flux at the point of disconnect than standard motors. It is for this reason that the energy efficient machines have a larger residual voltage at the point of disconnect. However, the speed of the decay of the residual flux of the standard efficiency machine is higher than the energy efficient machine and, as a result, the energy efficient machine resulted with a higher residual voltage at the 180° phase shift. This leads to a larger potential difference for the energy efficient machines than the standard efficiency machines. However, the stator impedance of the energy efficient machine was established as a dominating factor in the outcome of the tests results. Energy efficient machines have a significantly lower impedance than standard efficiency machines and due to this, they are more susceptible to the detrimental effects of out-of-phase restarting. It was important to establish a critical point when the current and torque transients are at a maximum as the motors speed is winding down. It is necessary to minimise the effects of restarting at this critical point as the resulting developed torque can be mechanically detrimental to the shaft. The residual voltage needs to be minimised dramatically to a point where the out-of-phase reclosing will not give rise to significantly high torque transients. Additional to this study was the observation of the current and torque transients in the presence of voltage unbalance. Voltage unbalance presents a power quality issue which can potentially have a negative effect on the efficiency of an induction machine. Both machines were tested for 0%, 1% and 2% voltage unbalance with a focus on start-up and 180° restart. In addition, voltage unbalance was introduced at the rated voltage of 400 V with 10% variations above and below this rating for over and undervoltage respectively. It was seen that the energy efficient machines were more vulnerable to unbalance effects due to a larger negative sequence air gap torque being developed under transient conditions.